2021
DOI: 10.3390/math9222893
|View full text |Cite
|
Sign up to set email alerts
|

Research on Dynamic Response Characteristics for Basement Structure of Heavy Haul Railway Tunnel with Defects

Abstract: Based on the basic principle of thermodynamics, an elastoplastic damage constitutive model of concrete is constructed in this paper. The model is realized and verified in FLAC3D, which provides a solid foundation for the study of dynamic response and fatigue damage to the base structure of a heavy haul railway tunnel. The dynamic response and damage distribution of the base structure of a heavy-duty railway tunnel with defects were numerically simulated by the concrete elastic-plastic damage constitutive model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…(6) After the steel arch frame was erected, M20 cement mortar was used to fll the chisel groove and the gap between the profle steel fange and the concrete lining surface to bring the frame close to the original concrete lining and give full play to its bearing capacity. (7) Inspect the welds between the sections of the original steel arch and repair and strengthen those that failed to meet the requirements. ( 8) Short anchor bolt with 20 mm in diameter threaded reinforcement with a circumferential spacing of 0.5 m was welded with steel plate and anchored in the lining using a coil anchoring agent.…”
Section: Specifc Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) After the steel arch frame was erected, M20 cement mortar was used to fll the chisel groove and the gap between the profle steel fange and the concrete lining surface to bring the frame close to the original concrete lining and give full play to its bearing capacity. (7) Inspect the welds between the sections of the original steel arch and repair and strengthen those that failed to meet the requirements. ( 8) Short anchor bolt with 20 mm in diameter threaded reinforcement with a circumferential spacing of 0.5 m was welded with steel plate and anchored in the lining using a coil anchoring agent.…”
Section: Specifc Stepsmentioning
confidence: 99%
“…Han et al [6] developed a treatment technology for optimizing the stress state of railway tunnel bottom structure. Chai [7,8] analyzed the dynamic response characteristics for basement structure of heavy-haul railway tunnel with defects and researched the multijoint rock failure mechanism based on moment tensor theory.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [ 35 ] presented a damage-constitutive equation based on irreversible thermodynamics, but the equation did not explicitly express the damage variable. Based on the damage and flow criterion, Chai [ 36 ] deduced the damage variable in the framework of the elastic–plastic theory. He et al [ 37 ] introduced the damage function potential and built empirical expressions of the damage variable related to temperature and material property.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [26,27] studied the evolution law of the voiding of surrounding rock with different soil qualities (cohesive soil, pebble soil, and sandy soil) for a tunnel base using field monitoring and model tests, and they found that the cohesive soil was most affected by the train load and groundwater. Chai [28] used the finite difference software FLAC3D to study the dynamic response and structural damage of a tunnel base structure with different degrees of bedrock softening.…”
Section: Introductionmentioning
confidence: 99%